IMPROVING THE OPERATIONAL TECHNICAL SKILLS OF LIVESTOCK EQUIPMENT AT INDRAPURI BPTU-HPT - Zulkifli, Zulkifli; Ningsih, Dede Alfi; Armayanti, Febi; Farhan, Muhammad; Johani, Johani (Journal of Social Comunity Services, 2025)
Objective: BPTU -HPT Indrapuri is one of the places for refining Aceh cattle and procuring green fodder seeds. Indrapuri BPTU-HPT also functions as a place for Field Practice, Field trips, and student research. Along with the development of technology and digitalization in the world of animal husbandry, it is necessary to conduct field visits for students. These field visits aim to better understand the knowledge and use of livestock machinery. Method: Students visited Indrapuri BPTU-HPT in order to observe and interview officers operating livestock equipment. The methodology for implementing field visits to the use of livestock operational machinery at Indrapuri BPTU-HPT is carried out by holding field practicums on livestock operational machinery. Results: The study found that Indrapuri BPTU-HPT uses various types of livestock operational machines such as feed choppers, feed mixers, milkers, manure vacuum cleaners, and egg incubators to support livestock activities. The machines serve specific functions: the chopper cuts the greens, the mixer mixes the feed, the milker facilitates hygienic milking, and the manure vacuum cleaner cleans the cage. The use of these machines brings several advantages, including time efficiency, improved product quality, and labor reduction. However, challenges such as high costs, maintenance, and electricity dependence remain. These operational machines play a significant role in increasing productivity and efficiency by enabling faster feed provision and cleaner cages, which contribute to the improved purification of Aceh cattle and the overall quality of livestock feed at Indrapuri BPTU-HPT. Novelty: The development of livestock tools and machinery is advancing continuously. Therefore, students, in addition to studying on campus, need to gain practical experience in the field of animal husbandry. This helps them to better understand the use of tools and machinery, as well as to gain insights into livestock feed preservation and livestock care management. This hands-on learning through field visits provides students with valuable knowledge and skills that will prepare them for their future careers.